FAKTOR FAKTOR RASIO FUNDAMENTAL PERUSAHAAN DALAM MEMENGARUHI HARGA SAHAM (Studi pada Perusahaan Multisektor yang Terdaftar Pada Indeks IDX-30 Tahun 2016-2020) - Pratama, Andra Wisnu; Marsono, Marsono (Diponegoro Journal of Accounting, 2021)
The capital market is an industry that has been developed for decades. The instruments that are always traded in the capital market are stocks. The IDX has several indexes in the stock market. One of the indexes that is interesting to study is the IDX-30 Index because it is proven to be sustainable and the liquidity of its financial statements and stock performance are attractive. This study aims to examine the effect of NPM, ROA, DER, EPS, and PBV on stock prices in companies listed on the IDX-30 Index 2016-2020 on the Indonesia Stock Exchange. Stock prices can be influenced by many factors, including the fundamentals contained in the company's financial statements. The variables used in this study were NPM, ROA, DER, EPS and PBV as independent variables. With Stock Price used as the dependent variable. The population and sample in this study are companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The number of samples is a total of 19 companies that are included in the IDX-30 Index. The research method data analysis used in this study was multiple linear regression analysis and SPSS version 25 application for windows to find the effect of regression. This study used Signal theory to formulate research hypotheses. The results showed that there was a significant positive effect of NPM on stock prices, ROA had a significant negative effect on stock prices, DER had a significant negative effect on stock prices, EPS had a significant positive effect on stock prices, while PBV had a significant positive effect on stock prices.